Metabolic capabilities of Actinobacillus succinogenes for succinic acid production - Rafieenia,R. (2014)
Attention has been focused on microbial succinic acid production as an alternative for conventional chemical synthesis that is associated with environmental pollution. A metabolic model for Actinobacillus succinogenes 130Z was developed with a mixture of glucose and xylose as substrate. The metabolic fluxes during succinicate production were determined using flux balance analysis by linear programming optimization in the MATLAB environment. Different glucose ratios (0.3, 0.4 and 0.7 mol.mol-1substrate) were used as model assumptions to calculate optimal fluxes, maximum growth and succinate production. The model revealed that higher growth rates and product yields were correlated with higher glucose content in the substrate mixture. When glucose constituted 0.5 mol.mol-1 substrate, a lower succinate yield (0.64 mol.mol-1 substrate) was obtained, compared to 0.73 mol.mol-1 substrate when glucose was used individually. Deletion of different unessential reactions in the model showed that a knockout of the acetate formation pathway would increase the succinate yield by 21% when glucose and xylose were used in equal molar ratios.